Mediasi Brand Trust pada Pengaruh Brand Personality terhadap Brand Loyalty - Putri , Wiwi Rahayu; Bastian, Adolf; Handayani, Ririn (CV. ITTC INDONESIA, 2024)
This study uses a quantitative method with a descriptive and explanatory survey approach. The study was conducted at RS. Ibnu Sina Pekanbaru, with the aim of testing the role of brand trust in mediating brand personality towards brand loyalty. The population of this study consisted of directors, general managers, medical support managers, PPI (infection control center), purchasing, pharmacy, and users (doctors, nurses and midwives) totaling 130 people. Based on this population size, according to the Krejcie and Morgan table (1970), the sample size for this study was 97 people. The sampling method used in this study was Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. The results of the study show that brand personality does not have a significant effect on brand loyalty, brand personality has a significant positive effect on brand trust, brand trust has a significant positive effect on brand loyalty, and brand trust mediates the effect of brand personality on brand loyalty.